The Explanatory, Social, and Performative Power of Gun Imaginaries - Heiskanen Benita; Kolehmainen Pekka M. (Brill, 2022)
The concluding chapter wraps up the volume by pointing to the explanatory, social, and performative aspects of gun imaginaries, as understood through the various historical contexts and interpretive lenses that the contributors engage. The transdisciplinary American Studies explications of gun debates demonstrate the great significance invested in weapons culture in the United States, be it on societal, cultural, or academic levels. Guns as imaginaries galvanize individuals who are up in arms, while their actions and reactions reverberate into further imaginaries; thus, individuals and communities simultaneously shape and are shaped by the broader power relations that they are necessarily a part of. Ultimately, the exploration of Texas as a gun imaginary and guns as a Texan imagery provides a toolbox and a roadmap for future discussions of the significance of firearms in other geographic contexts beyond the United States.
Up in Arms: Gun Imaginaries in Texas